2014
DOI: 10.1021/cg501128n
|View full text |Cite
|
Sign up to set email alerts
|

Syntheses, Structures, and Magnetic Properties of Three Manganese(II)-Octacyanotungstate(V) Bimetallic Compounds with Linear Ligands

Abstract: Three manganese(II)-octacyanotungstate(V) bimetallic compounds, [Mn(H 2 O) 2 (dpe)] 3 [W(CN) 8 ] 2 ·2dpe·7H 2 O (dpe = trans-1,2-di(4-pyridyl)ethene) (1), [Mn(H 2 O) 2 (azpy)] 3 [W(CN) 8 ] 2 ·3azpy·4H 2 O (azpy = 4,4′-azopyridine) (2), and [Mn(H 2 O) 3 (azpy)] 2 [Mn(CH 3 CN) 2 (azpy)][W-(CN) 8 ] 2 ·5azpy·2H 2 O (3) were prepared by in situ or secondary assembly methods. Compounds 1 and 2 show three-dimensional (3D) networks through the cross-link of one-dimensional (1D) infinite 3,2-chains or ropeladder chains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 46 publications
(62 reference statements)
0
12
0
Order By: Relevance
“…The equatorial plane and apical sites are all occupied by water molecules with Mn–O distances of 2.100–2.391 Å. The coordinated arrangement and parameters of Mn2 were relatively common in the M V/IV (CN) 8 ‐Mn II compounds , . Subsequently, the central Mo1 and Mn1 atoms are linked alternatively by CN groups, generating a 2D waved grid‐like layer (Figure b, Figure c), as found in (tetrenH 2 ) 0.5 [Mn II (H 2 O) 2 ][Mo V (CN) 8 ] · 2H 2 O and {(tetrenH 5 ) 0.8 Cu II 4 [W V (CN) 8 ] 4 · 7.2H2O} n .…”
Section: Resultsmentioning
confidence: 96%
“…The equatorial plane and apical sites are all occupied by water molecules with Mn–O distances of 2.100–2.391 Å. The coordinated arrangement and parameters of Mn2 were relatively common in the M V/IV (CN) 8 ‐Mn II compounds , . Subsequently, the central Mo1 and Mn1 atoms are linked alternatively by CN groups, generating a 2D waved grid‐like layer (Figure b, Figure c), as found in (tetrenH 2 ) 0.5 [Mn II (H 2 O) 2 ][Mo V (CN) 8 ] · 2H 2 O and {(tetrenH 5 ) 0.8 Cu II 4 [W V (CN) 8 ] 4 · 7.2H2O} n .…”
Section: Resultsmentioning
confidence: 96%
“…Previous magneto‐structural investigations on the single cyanido‐bridged Mn II ‐octacyanotungstate(V) pathway revealed the occurrence of antiferromagnetic interactions up to –39 cm –1 ,, , the spin Hamiltonian being defined as H = – J S W S Mn . It was found that the magnetic coupling in this system depends on the structural parameters such as the type of coordination polyhedron of the [W(CN) 8 ] 3– metalloligand and parameters within the cyanide‐bridged linkage (Mn–N bond length, Mn–N–C bond angle and Mn ··· W separation) .…”
Section: Resultsmentioning
confidence: 99%
“…Classic examples are the systems containing Cu II and Mn II bridged by oxamato or oxamido ligands , . Since the first report on a ferrimagnetic chain in the early '80s by Verdaguer, the ferrimagnetic strategy was applied and developed for other examples of bimetallic monodimensional complexes , . Examples of d–d and d–f ferrimagnetic heterobimetallic chains based on cyanido metalloligands are still limited.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In light of the above challenges, herein, we have synthesized a new heterometallic Na/Co-based MOF ( 1 ), [Na 2 Co­(SDCA)­( μ 2 -OH) 2 ( μ 2 -H 2 O) 2 (Azopy)] n , by a facile mixed ligand strategy using 2,5′-thiophenedicarboxylic acid (H 2 SDCA) and 4,4′-azopyridine (Azopy) by slow-diffusion technique at room temperature. It is well-known that multicarboxylate linkers are repeatedly preferred due to their multi coordination manners through the complete/partial deprotonation of −COOH groups in the construction of MOFs. Here, SDCA is chosen due to its multicoordination ability with metal center through the −COO – group to deliver unique structure with fascinating properties and also its derivatives are widely employed as electrode materials , while the auxiliary pillared Azopy linkers embody the 4-pyridyl building elements, are usually employed as pillars for the extension of frameworks with good flexibility/stability, and the presence of delocalized π-electrons in the pyridyl rings are also accomplished to encourage the electrical conductivity in the resulting MOFs. Therefore, 1 was expected to give a synergistically enhanced supercapacitor performance with excellent cycling stability, which is also a central idea of the present work.…”
Section: Introductionmentioning
confidence: 99%